Diabetics suffer in silence – about sexual dysfunction and modern therapeutic possibilities in diabetes mellitus - Madej, Karolina; Krawiec, Paulina; Wolanin, Izabela; Zielonka, Bartłomiej; Kowalczyk, Ilona; Stachyra, Bartłomiej; Wolanin, Marta; Stawikowski, Cezary; Dengler, Barbara; Osińska, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction Nowadays, the global incidence of diabetes is on the rise, indicating a growing medical concern due to the persistent increase in cases. This disease is insidious and silent. Despite its long-term asymptomatic course, it secretly damages many organs, leading to distant and often irreversible complications. Early diagnosis of asymptomatic patients with risk factors, the use of screening tests, as well as appropriate control of the disease can significantly delay the process of developing complications; ensuring a longer and better quality of life for patients. A seriously problematic, but rarely discussed, disorder, experienced by some within the male patient group, is erectile dysfunction. Understanding the pathophysiology and the mechanism responsible for this disorder enables early prevention and taking appropriate steps, implementing effective therapy; thus – enhancing and prolonging sexual function and enhancing quality of life of patients with diabetes. Purpose of the work This article reviews the state of knowledge based on available research on sexual dysfunction in men with diabetes. The purpose of this review is to present the general issues, pathophysiology, risk factors and contemporary therapeutic options for sexual dysfunction disorders in this group of patients. Materials and methods The authors based on databases such as PubMed, Scopus anf Google Scholar, created a work summarizing review of currently available publications on the issue of erectile dysfunction in patients with diabetes mellitus. The authors using the terms contained in the „keywords” column, searched for available information contained in other scientific works, on the basis of which they created the above review.